MODERN APPROACHES TO DEVELOPING THE FINANCIAL POTENTIAL OF THE REGION - Akramov Golibjon Bahodir ugli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article examines modern approaches to the development of the financial potential of the region. In particular, scientific proposals and practical recommendations have been developed on important issues such as revealing the economic and social essence of the concept of financial potential, factors affecting the formation of regional gross domestic product, determining the synergistic effect of inter-budgetary relations in the region, rational use of financial resources.